Factor Affecting Customer Satisfaction on Online Shopping in Kathmandu Valley - Sharma, Asmita; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2025)
This study examines the factor affecting customer satisfaction on online shopping in Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are price fairness, delivery speed, product quality, payment method, delivery cost, and perceived usefulness. The primary source of data is used to assess the opinions of respondents regarding rice fairness, delivery speed, product quality, payment method, delivery cost, perceived usefulness, and customer satisfaction. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of customer satisfaction on online shopping in Kathmandu Valley. The study showed a positive impact of price fairness on customer satisfaction. It indicates that price of a comparative other party is reasonable, acceptable, or justifiable leads to increase in customer satisfaction. Similarly, the study showed a positive impact of delivery speed on customer satisfaction. It indicates that higher the delivery speed, higher would be the customer satisfaction. Likewise, the study revealed a positive impact of product quality on customer satisfaction. It indicates that higher the product quality, higher would be the customer satisfaction. Further, the study showed a positive impact of payment method on customer satisfaction. It indicates that the various options available for customers to make payments when purchasing a product or service leads to increase in customer satisfaction. In addition, the study showed a positive impact of delivery cost on customer satisfaction. It indicates affordable delivery cost leads to increase in customer satisfaction. Moreover, the study showed a positive impact of perceived usefulness on customer satisfaction. It indicates that higher the subjective perception of users, higher would be the customer satisfaction.